Studi Variasi Konsentrasi NaOH dan H2SO4 Untuk Memurnikan Silika Dari Abu Sekam Padi Sebagai Adsorben Ion Logam Pb2+ dan Cu2+ - Harimu, La; Rudi, La; Haetami, Aceng; Santoso, Giswa Ayu Pratiwi; ., Asriyanti (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2019)
A study of variations in the concentration of NaOH and H2SO4 to purify silica from rice husk ash and its application as adsorbent of Pb2+ and Cu2+ Metal Ions. The NaOH concentrations used were 8%, 9%, 10%, 11%, 12% and 13% and H2SO4 concentrations were 5.4%, 8.16%, 10.88%, and 13.61%. The process of adsorption of Pb2+ and Cu2+ metal ions was carried out at pH (3, 4, 5, 6) and silica masses. The results showed the silica yield obtained in the form of white powder. The highest silica content at 12% NaOH concentration of 41.81% with a purity of 89.09% and H2SO4 concentration is 10.88% at 65.39% with a purity of 94.94% initial content 86.02%. The results of surface structure characterization using Scanning Electron Microscope (SEM) average size of particle diameter was 0.030 Âµm. Optimal adsorption process of Pb2+ and Cu2+ metal ions using silica from rice husk occurred at pH 6 and the adsorbent mass was 0.3 gram, the adsorption efficiency was 98% and 86.25% respectively with adsorption capacity of 0.96 mg/g for metal Pb2+ and 0.83 mg/g for Cu2+ metals.